Perkembangan Religiusitas Anak Generasi Alpha Dalam Konteks Pendidikan Di Era Digital - Inayah Noor Wahidah; Muhammad Rizqi Bahrain; Alya Nurussyifa; Anggi Suwito; Surawan (Indonesian Journal of Islamic Education Studies (INJURIES), 2026)
Generation Alpha is a group born since 2010 and growing up in an environment closely linked to the development of digital technology. This situation has a significant influence on the formation of children's religiosity, both in terms of religious knowledge (cognitive), attitudes and experiences (affective), and religious practices in daily life. This study aims to examine the development of religiosity in Generation Alpha children in the context of education in the digital age and to identify the various challenges and opportunities arising from the use of technology in religious learning. This study uses a qualitative approach through library research, utilizing various sources such as scientific journals, books, and relevant previous research. The study's findings indicate that the digital era offers ample opportunities to enhance children's religiosity through the use of technology-based learning media, digital da'wah content, and easy access to religious information. However, the presence of inappropriate content, interference from social media, and a lack of guidance from parents and teachers have the potential to hinder the internalization of religious values. Therefore, harmonious collaboration between families, educational institutions, and the community is needed to develop religiously oriented digital literacy and adaptive learning strategies to ensure that the religious development of Generation Alpha children remains aligned with Islamic values.